2015
DOI: 10.1016/j.jconhyd.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of trace organic chemicals during groundwater recharge: How useful are first-order rate constants?

Abstract: This study developed relationships between the attenuation of emerging trace organic chemicals (TOrC) during managed aquifer recharge (MAR) as a function of retention time, system characteristics, and operating conditions using controlled laboratory-scale soil column experiments simulating MAR. The results revealed that MAR performance in terms of TOrC attenuation is primarily determined by key environmental parameters (i.e., redox, primary substrate). Soil columns with suboxic and anoxic conditions performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 41 publications
8
68
2
Order By: Relevance
“…This is clear evidence for inadequate wastewater management in these areas. Caffeine, theophylline and cotinine are usually degradable to a high degree during RBF [37][38][39][40]. This fact was confirmed within this study for Delhi, Mathura and Agra (Appendix A Table A2), Haridwar, Srinagar and Karnaprayag (Appendix B Table A4).…”
Section: Other Micropollutantssupporting
confidence: 83%
“…This is clear evidence for inadequate wastewater management in these areas. Caffeine, theophylline and cotinine are usually degradable to a high degree during RBF [37][38][39][40]. This fact was confirmed within this study for Delhi, Mathura and Agra (Appendix A Table A2), Haridwar, Srinagar and Karnaprayag (Appendix B Table A4).…”
Section: Other Micropollutantssupporting
confidence: 83%
“…This could be explained by either the lower active biomass on the soil in the current study (ATP ¼ 70 ng cm À3 ) compared to the previous study (ATP ¼ 109e135 ng cm À3 ), the different redox conditions (nitrate reducing versus oxic conditions in the previous study), or a combination of both. Regnery et al (2015b) demonstrated that acetaminophen removal was not affected by redox conditions, thus the most plausible explanation for the lower OMP biodegradation rates observed in this study is the lower quantity of active biomass.…”
Section: Omp Removalmentioning
confidence: 51%
“…Besides, the pathogen indicators (total coliforms and E. coli) were also measured along the reference system and compared to those obtained for the systems operating with the two reactive barriers to assess the efficiencies of these designs. Figure 3 shows the comparison among the estimated degradation rates, λ (A), and retardation coefficients, R (B), at Sant Vicenç dels Horts and those reported from other studies carried out both in laboratory experiments and at field sites [54][55][56][57][58][59][60][61][62]. Considering the typical maximum duration for columns (1-2 years) and field experiments (10-20 years), the minimum value for λ was allowed to be 10 −3 , and 10 −4 d −1 , respectively, following the approach from Greskowiak et al [63].…”
Section: Assesing the Reactive Barrier Efficiencymentioning
confidence: 95%